Analisis Strategi Penjualan Stok Spare Part di PT. Fajar Mas Murni Surabaya - Ida Purwanti; Yuniar Farida (Jurnal Matematika MANTIK, 2018)
This research uses a case study at PT Fajar Mas Murni Surabaya which aims to classify item of spare parts inventory with a BCG matrix approach to determine sales strategy of spare part inventory. The classification results with BCG matrix obtained 6,60% items included in quadrant stars which contributed 80,67% turnover for the company; 15,57% items included in the question marks quadrant which contributed 14,95% turnover for the company; 71,70% items included in the quadrant dogs which contributed only 1,87% turnover for the company; and 6,13% is included in the cash cows quadrant which contributes a 2,50% turnover for the company. The strategy analysis that should be carried out (1) on the stars quadrant is to forecast the sales to maintain the continuity of spare part inventory, (2) on the question marks quadrant is to develop the sales by selling items at a discount so that can increase sales volume and can spend inventory, (3) on the dogs quadrant is to further enhance the promotion activities of these items, (4) on the cash cows quadrant is to maintain sales. Then sales forecasting is carried out on stars quadrant spare parts inventory in 2018 so that continuity is maintained by using the Trend (t) moving average ratio method with Cycle variation (C), Season variation (S), and Irregular movement (I), which obtained MAPE value of 23%. If only using Trend, it obtained greater MAPE value of 27%.